Análisis del estado de conservación de zonas riparias en la diversidad de macroinvertebrados acuáticos en la Hoya de Loja. - Capa Cobos, Karina Lisseth (2019)
The presence of fluvial riparia vegetation is of great importance in the functioning of the water system; Its maintenance and conservation is closely related to the ecological condition of rivers, the quality of water and the communities of aquatic macro-invertebrates. However, over time, these areas are increasingly unprotected, mainly affected by increased pastures, agriculture and livestock. Therefore, the present study seeks to evaluate the conservation status of the Riparia area of the Microwatersheds El Carmen, Mónica and Las Violetas (preserved, semi-conserved and not conserved respectively) and the relationship with their diversity of aquatic macro-invertebrates. For which 17 metrics were calculated, among them, indices of biological quality of the water (ABI and IMEERA B). For each one, a riparian transect of 500 m was established at length of the river, where the macro-invertebrates were collected at eight different points, and in a central riparian sub-transect of 10 x 200m within 500m, the vegetation quality Protocol was applied Ribera (CBR index). The microwatershed El Carmen and Mónica (conservation states conserved and semipreserved respectively) despite presenting different quality of Ribera according to the index CBR, presented relatively similar results, with greater diversity, evenness and lower Number of pollution-tolerant taxa; Unlike the microwatershed Las Violetas (with unpreserved State of conservation) presented significant differences, mainly in abundance, less diversity and dominance of species. The external impacts on the riverbanks are different in each water system, however it was reflected in the water quality. Key words: Riparian vegetation, conservation status, aquatic macro-invertebrates.